2014
DOI: 10.1111/apha.12289
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional reconstruction of the human skeletal muscle mitochondrial network as a tool to assess mitochondrial content and structural organization

Abstract: Two microscopy methods to visualize skeletal muscle mitochondrial networks in 3D are described and can be used as tools to investigate mitochondrial dynamics in response to life-style interventions and/or in certain pathologies. Our results question the classification of mitochondria into subsarcolemmal and intermyofibrillar pools, as they are physically interconnected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 33 publications
4
75
0
Order By: Relevance
“…Although connected to the IMF pool (14), SS mitochondria comprise only 20% of myocellular mitochondria and are located distal to most myofilaments. However, compared with the IMF pool, SS mitochondria are more responsive to the effects of muscle use/disuse (2,3,27,36,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although connected to the IMF pool (14), SS mitochondria comprise only 20% of myocellular mitochondria and are located distal to most myofilaments. However, compared with the IMF pool, SS mitochondria are more responsive to the effects of muscle use/disuse (2,3,27,36,47).…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with the IMF pool, SS mitochondria are more responsive to the effects of muscle use/disuse (2,3,27,36,47). Moreover, because of their close proximity to myonuclei (14,19), alterations in SS content and/or function that affect energy supply (40), reactive oxygen species production (55), and/or apoptotic stimuli (2, 3) may alter nuclear gene transcription in ways that modulate myofilament and/or mitochondrial function throughout the cell. This could occur through an effect of SS mitochondria to modulate myonuclear number, as animal models show that SS mitochondria produce more apoptotic stimuli in response to disuse (2), and it has been suggested that loss of myonuclei contributes to muscle atrophy (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, this technology is not available to all research labs and is not ideal for in vivo studies. To address the significance of mitochondrial morphology in tissue, 3-dimensional (3-D) reconstructions using either confocal microscopy or electron microscopy provide evidence that the subsarcolemmal (SS) and intermyofibrillar (IMF) mitochondrial membranes physically interact in mouse and human skeletal muscle (Dahl et al, 2015; Picard et al, 2013). A recent paper extends these studies using quantitative 2-D transmission electron microscopy (TEM) to show that fusion indexes (Mfn2:Drp1 ratio) increase in aged muscle, possibly related to changes in mitochondrial morphology that contribute to mitochondrial dysfunction and sarcopenia (Leduc-Gaudet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently used dSTORM for the first time in a recent study to characterise the nano-architecture of the previously detected subsarcolemmal components 56 of the mammalian skeletal muscle ttubules that had been filled with fixable fluorescent dextrans. 37 Facilitating the fast propagation of action potentials, 57 buffering ion exchange between the external space and deeper t-tubules and/or communication with the tubular extensions of subsarcolemmal mitochondria (recently visualised with deconvolved confocal micrographs and focused ion beam SEM reconstructions 58 ) are all possible functional roles of these tubules. dSTORM images of deeper tubules in rat skeletal muscle have since emerged, 59 although quantitative measurements are yet to be described.…”
Section: Fig 3 Comparison Of Micron-and Nanometre-scale Morphologies mentioning
confidence: 99%